Primary Health Service Integration Policy as a Key Strategy to Achieve Universal Health Coverage (UHC): Primary Health Service Integration Policy - Permatasari, Putri; Hardy, Fathinah Ranggauni; Setiawati, Marina Ery (Jurnal Kesmas Jambi, 2025)
Integration of primary health care services is an approach that combines various health services, both at the prevention, treatment, and rehabilitation levels, into one integrated system framework. This study aims to ensure the policy better coordination between service providers, minimize resource waste, and improve accessibility and quality of health services for the wider community. Literature review with articles from the last 5 years, free-full text, using predetermined keywords, and utilizing 2 databases, namely Google Scholar and PubMed. Findings indicate that the implementation of the UHC policy through the National Health Insurance (JKN) program in Indonesia has not been effective and still faces challenges. The WHO recommends PHC as a community health approach that focuses on meeting the needs of the community from prevention efforts to treatment or rehabilitation. Strengthening primary health care services is very effective in supporting the achievement of Universal Health Coverage (UHC) targets in Indonesia. Implementation of the UHC Policy through the National Health Insurance (JKN) program in Indonesia has not been effective and still faces challenges. The WHO recommends PHC as a health approach to the community that focuses on meeting community needs from prevention efforts to treatment or rehabilitation. Strengthening primary health services is very effective in supporting the achievement of the Universal Health Coverage (UHC) target in Indonesia. This study highlights the challenges faced by UHC in Indonesia are budget constraints, infrastructure, and human resources, which impact the quality of healthcare services.